BOOSTING PSYCHOLOGICAL WELL BEING OF ADOLESCENT: PSYCHONEUROBIC INTERVENTION VERSUS MINDFULNESS TRAINING - Gupta, Aditi (PEOPLE: International Journal of Social Sciences, 2018)
Dwelling on the mental health issues of society in general and youth in particular, the WHO report (2009/10) estimated that approximately one in five young people under the age of 18 experience some form of developmental, emotional or behavioural problems. With an estimated 1.2 billion young people aged 10-19 years in the world, the problem requires substantial consideration of mental health experts, behavioural scientists and policy makers. With this consideration, the present study attempts to investigate the effectiveness of two types of intervention strategies– Psycho-neurobics and Mindfulness meditation on the psychological well-being of high school students aged 15 to 17 years in Delhi-NCR, India. The quasi-experimental design examined the effect of 4 months mindfulness training and psycho-neurobic training as compared to control group on pre-identified adolescent exhibiting low psychological well-being. Analysis of Variance and Pearson correlation revealed both treatment groups experienced significant increase in psychological well being. However, significant difference emerged in improvement trajectory of different domains of psychological well-being where psycho-neurobic treatment yielded greater effectiveness. The study empirically demonstrates psycho-neurobics as an effective intervention that can be integrated with school curriculum in Indian subpopulation.